Side effects may include strangers - Parisien, Dominik (Hugh MacLennan poetry series., 2020)
"To be ill is to be a body bursting with strangers. A curiosity. A narrative to interpret. Dominik Parisien's debut collection is a poignant celebration of the complicated lived experience of disability, a challenge to the societal gaze, and a bold reconfiguration of the language of pain. A powerful contribution to the field of disability poetics, Side Effects May Include Strangers is an affecting look at the multitude of ways a body is both boundary and boundless. Parisien takes bpNichol's claim that "what is a poem is inside of your body" and localizes the inner and outer lives of disabled, queer, and aging bodies as points of meaning for issues of autonomy, disability, sexuality, and language. Balancing hope and uncertainty, anger and gratitude, these poems shift from medical practice to myth, from trauma to intergenerational friendship, in an unflinching exploration of the beauty and complexity of othered bodies."--